Contrasting genetic diversity of tree species in Spain: from Tertiary relicts to domestication - Lopez de Heredia, U.=700 1 Robledo Arnuncio, J.J.; Fuentes Utrilla, P.; Valbuena Carabana, M.; Gil, L.
(Es, En)
ilus., 76 ref.
Keywords: ECOSISTEMA; VARIACION GENETICA; MARCADORES GENETICOS; BIOGEOGRAFIA; ECOLOGIA FORESTAL; ESPAÑA